Scheduled Telephone Support for Internet Cognitive Behavioral Therapy for Depression in Patients at Risk for Dropout: Pragmatic Randomized Controlled Trial - Pihlaja, Satu; Lahti, Jari; Lipsanen, Jari Olavi; Ritola, Ville; Gummerus, Eero-Matti; Stenberg, Jan-Henry; Joffe, Grigori (JMIR Publications, 2020)
BackgroundTherapist-supported, internet-delivered cognitive behavioral therapy (iCBT) is efficient in the treatment of depression. However, the optimal mode and intensity of therapist support remain to be identified. Scheduled telephone support (STS) may improve adherence and outcomes but, as it is time- and resource-consuming, should be reserved for patients for whom the usual support may be insufficient. ObjectiveThis paper aims to reveal whether add-on STS for patients at risk of dropping out improves treatment adherence and symptoms in iCBT for depression. MethodsAmong patients participating in an ongoing large observational routine clinical practice study of iCBT for depression delivered nationwide by Helsinki University Hospital (HUS-iCBT), those demonstrating a ≥14-day delay in initiation of treatment received invitations to this subsidiary STS study. A total of 100 consenting patients were randomly allocated to either HUS-iCBT as usual (control group, n=50) or HUS-iCBT plus add-on STS (intervention group, n=50). Proportions of those reaching midtreatment and treatment end point served as the primary outcome; secondary outcomes were change in Beck Depression Inventory (BDI)-measured depressive symptoms and time spent in treatment. ResultsAdd-on STS raised the proportion of patients reaching midtreatment compared with HUS-iCBT as usual (29/50, 58% vs 18/50, 36%; P=.045) and treatment end point (12/50, 24% vs 3/50, 6%; P=.02). Change in BDI score also favored add-on STS (3.63 points vs 1.1 points; P=.049), whereas duration of treatment did not differ. ConclusionsAdd-on STS enhances adherence and symptom improvement of patients at risk of dropping out of iCBT for depression in routine clinical practice. Trial RegistrationInternational Standard Randomised Controlled Trial Number (ISRCTN) 55123131; http://www.isrctn.com/ISRCTN55123131.